Development of an HIV risk reduction counselling intervention for use in South African sexually transmitted infection clinics - Vuyisile Mathiti; Leickness C. Simbayi; Sean Jooste; Queen Kekana; Xolani P. Nibe; Luvuyo Shasha; Philasande Bidla; Pamela Magubane; Demetria Cain; Charsey Cherry; Seth C. Kalichman (Taylor & Francis Group, 2005)
South Africa urgently needs HIV prevention interventions that can be disseminated for use in clinical and community settings. A brief theory-based HIV risk reduction counselling intervention originally developed in the USA has recently been adapted for use in a South African sexually transmitted infection clinic. The 60-minute risk reduction counselling intervention was grounded in the Information-Motivation-Behavioural Skills (IMB) model of HIV preventive behaviour change, adapted through a series of interdisciplinary collaborative workshops. This paper reports the process of developing and culturally adapting the brief risk reduction counselling intervention. The processes used for adapting the HIV risk reduction counselling for South Africa provides a potential model for conducting technology transfer activities with other HIV prevention interventions. Several lessons learned from this process may help guide future efforts to transfer HIV prevention technologies.